2021
DOI: 10.3390/jcm10194344
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP as a Potential Marker of Cardiovascular Damage in Children with Chronic Kidney Disease

Abstract: Assessing cardiovascular disease (CVD) in children with chronic kidney disease (CKD) is difficult. Great expectations have been associated with biomarkers, including the N-terminal pro-brain natriuretic peptide (NT-proBNP). This study aimed to determine the correlation between NT-proBNP and cardiovascular complications in children with CKD. Serum NT-proBNP, arterial stiffness, common carotid artery intima-media thickness (cIMT), echocardiographic (ECHO) parameters (including tissue Doppler imaging), and bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(65 reference statements)
2
2
0
Order By: Relevance
“…In contrast, in a recent study on HD children, EF was not affected by HD and its values were not correlated to pre- and post-HD BNP levels [ 25 ]. Finally, although there are data supporting a positive correlation between BNP (or NT-proBNP) levels and systolic and/or diastolic blood pressure in CKD children, other studies showed, in accordance with our results, that NT-proBNP levels did not correlate with SBP or DBP [ 12 , 13 , 23 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, in a recent study on HD children, EF was not affected by HD and its values were not correlated to pre- and post-HD BNP levels [ 25 ]. Finally, although there are data supporting a positive correlation between BNP (or NT-proBNP) levels and systolic and/or diastolic blood pressure in CKD children, other studies showed, in accordance with our results, that NT-proBNP levels did not correlate with SBP or DBP [ 12 , 13 , 23 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…A significant inverse correlation was found, between BNP levels and eGFR and a positive one between BNP levels and CKD stage, serum creatinine and cystatin C levels. An increase in BNP or NT-proBNP levels with decreasing eGFR and increasing CKD stage has been reported in other studies [ 10 , 12 , 36 , 37 ]. In a study by Rinat et al, eGFR was an independent factor influencing BNP and NT-proBNP values [ 12 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Left ventricle mass index (LVMI) was calculated with parameters drawn from echocardiography (ECHO) measurements using M-mode assessment of the left ventricle with simultaneous recording of ECG in the second limb lead. The detailed methodology was described in our recently published manuscript [21]. Measurements were carried out with Philips iE33 device, using an S5-1 transducer (Philips, Amsterdam, the Netherlands).…”
Section: Echocardiography and Assessment Of Properties Of Arteriesmentioning
confidence: 99%